Polysemityper i ordförrådet - Norén, Kerstin (Nordiske Studier i Leksikografi, 2003)
In this article some lexical meaning extensions described in cognitive linguistics are compared to lexicographic definitions. The corpus consists of all words beginning with the letter k in a comprehensive modern Swedish dictionary, Nationalencyklopediens ordbok. The chosen meaning extensions are specialization, generalization, metonym and metaphor. The results show e.g. that specialization is by far the most common meaning extension in this corpus, metaphor by far the least common. Besides these quantiative figures, different semantic subgroups of the four extension types are recognized.